Vito Acconci and the use of the body as an artistic experience - Miranda, Giuliano de; Cirillo, Aparecido José (Revista do Colóquio, 2022)
This article will address, to some extent, the trajectory of the American visual artist Vito Acconci, mainly from the perspective of his performances. The artist is considered by many to be one of the precursors of the use of the body as an object of artistic experimentation, the so-called Body Art. To this end, we will shed light on some of his performance productions, which may reinforce this narrative, as well as outline his trajectory in the field of Arts, especially from the beginning of the 1970s, a period in which, apparently, there was a change of direction in Acconci’s artistic work.